MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOCITION (CIRC) DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN AKIDAH AKHLAK - Rasmuin Rasmuin; Siti Suwaibatul Islamiyah (Muróbbî: Jurnal Ilmu Pendidikan, 2020)
The purpose of this study was to determine the application of Cooperative Integrated Reading and Composition (CIRC) in improving grade 8 students learning outcomes in the subjects of the Akidah Akhlak MTs N Batu. This research is a classroom action research, which is a research that is situational, practical, and contextual based on the problems that arise in the learning activities of the Akidah Akhlak. This classroom action research was conducted in 3 cycles, namely pre cyle, cycle 1 and cycle 2. Based on the research that has been carried out, it can be concluded that the implementation of the learning of Akidah Akhlak by applying the cooperative integrated reading and composition (CIRC) learning model shows an increase in student learning outcomes. In the pre-cycle stage the average score reached 62.25 and only 12 students or 38.70% achieved mastery learning. Then in cycle 1 by applying the cooperative integrated reading and composition (CIRC) learning model the average value increased to 84.70 and there were 18 students or 58.06% who achieved mastery learning. Furthermore, in cycle 2 the average score increased to reach 94.77 and there were 21 students or 67.74% who achieved mastery learning.